Survival and infertility treatment in male cancer patients after sperm banking - Crha, Igor; Ventruba, Pavel; Žáková, Jana; Huser, Martin; Kubešová, Barbara; Hudeček, Robert; Jarkovský, Jiří (Fertility and sterility, 2009)
OBJECTIVE: To evaluate the relationship between sperm pathology and cancer diagnosis, determine the mortality rate, and evaluate the outcomes of the use of frozen sperm from the sperm bank. DESIGN: Prospective study. SETTING: University fertility center. PATIENT(S): A total of 619 male patients were referred for sperm freezing before gonadotoxic therapy from 1995 to 2006. INTERVENTION(S): Semen analysis, data verification in the National Oncologic Register, assisted reproduction technologies, and statistical evaluation. MAIN OUTCOME MEASURE(S): Cancer diagnosis and sperm pathology analysis, survival of patients, and infertility treatment success. RESULT(S): Malignant testicular cancer was diagnosed in 43.6% of patients, and malignant neoplasms of the lymphatic and hematopoietic tissues were found in 31.7% of patients. Azoospermia or severe oligospermia (<or=1 million/mL) was detected in 9.7% and 22.6% of patients, respectively. To date, 32 patients (5.2%) sought infertility treatment. Cryopreserved semen was used in 28 couples (87.5%), and 44 intracytoplasmic sperm injection (ICSI) cycles resulted in 13 pregnancies. In total, 74 deaths (11.9%) were reported, 61 of them (82.4%) within 30 months of the cryopreservation of their sperm. CONCLUSION(S): A significant number of patients survived. Intrauterine insemination and ICSI with cryopreserved sperm resulted in deliveries.
Keywords: Azoospermia; Infertility, Male; Semen Preservation; Sperm Banks; novorozenec; Retrospective Studies; sperma; Time Factors; Testicular Neoplasms; lidé; časové faktory; Freezing; azoospermie; spermabanky; Cryopreservation; uchování spermatu; intracytoplazmatické injekce spermie; Female; těhotenství; Neoplasms; mužská infertilita; Male; ženské pohlaví; Humans; testikulární nádory; mužské pohlaví; nádory; Semen; vedení porodu; Infant, Newborn; Pregnancy; Sperm Injections, Intracytoplasmic; Delivery, Obstetric; kryoprezervace; zmrazování; retrospektivní studie